Efektivitas Media Kotak Bicara untuk Meningkatkan Membaca Permulaan bagi Anak Autism Spectrum Disorder (ASD) (Single Subject Research di Kelas IV di SLB Tunas Harapan, Sawahlunto) - Vania Luthfiyah; Zulmiyetri Zulmiyetri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to test the effectiveness of the Talking Box learning media in improving early reading skills in children with Autism Spectrum Disorder (ASD), especially in composing more than one syllable into a word. The study used the Single Subject Research (SSR) method with an A-B-A design consisting of Baseline 1, intervention, and Baseline 2. The subject of the study was a fourth-grade ASD child at Tunas Harapan Special Needs School in Sawahlunto. Data collection techniques were carried out through observation, early reading ability tests, interviews with teachers and parents, and assessments of the child's abilities. Data were analyzed using visual analysis within and between conditions to see changes in children's reading abilities before and after the intervention. The results showed that the Talking Box media was effective in improving children's abilities in composing and reading simple words, such as table, book, ball, and hat. In addition, this media was able to create more interesting, interactive learning, and in accordance with the learning characteristics of children with ASD who require a visual and game-based approach. The implications of this study indicate that the Talking Box media can be used as an alternative learning method to help improve the early reading skills of children with ASD in special needs schools.